Reduced toxicity in the treatment of locally advanced rectal cancer: a comparison of volumetric modulated arc therapy and 3D conformal radiotherapy. Issue 1 (December 2015) - Dröge, Leif; Weber, Hanne; Guhlich, Manuel; Leu, Martin; Conradi, Lena-Christin; Gaedcke, Jochen; Hennies, Steffen; Herrmann, Markus; Rave-Fränk, Margret; Wolff, Hendrik
Abstract Background Excellent dosimetric characteristics were demonstrated for volumetric modulated arc therapy (VMAT) in preoperative chemoradiotherapy (CRT) for locally advanced rectal cancer (LARC). In a single-center retrospective analysis, we tested whether these advantages may translate into significant clinical benefits. We compared VMAT to conventional 3D conformal radiotherapy (3DCRT) in patients, homogeneously treated according to the control arm of the CAO/ARO/AIO-04 trial. Methods CRT consisted of pelvic irradiation with 50.4/1.8Gy by VMAT (n = 81) or 3DCRT (n = 107) and two cycles of 5-fluorouracil. Standardized total mesorectal excision surgery was performed within 4–6 weeks. The tumor regression grading (TRG) was assessed by the Dworak score. Acute and late toxicity were evaluated via the Common Terminology Criteria for Adverse Events and the Late effects of normal tissues scale, respectively. Side effects greater than or equal to grade 3 were considered high-grade. Results Median follow-up was 18.3 months in the VMAT group and 61.5 months in the 3DCRT group with no differences in TRG between them (p = 0.1727). VMAT treatment substantially reduced high-grade acute and late toxicity, with 5 % versus 20 % (p = 0.0081) and 6 % vs. 22 % (p = 0.0039), respectively. With regard to specific organs, differences were found in skin reaction (p = 0.019) and proctitis (p = 0.0153). Conclusions VMAT treatment in preoperative CRT for LARC showed the potential to substantially reduce high-grade acute and late toxicity. Importantly, we could demonstrate that VMAT irradiation did not impair short-term oncological results. We conclude, that the reduced toxicity after VMAT irradiation may pave the way for more efficient systemic therapies, and hopefully improved patient survival in the multimodal treatment of LARC.